Diagnostic and pathogenetic role of café-au-lait macules in nevoid basal cell carcinoma syndrome - Ponti, Giovanni; Tomasi, Aldo; Pastorino, Lorenza; Ruini, Cristel; Guarneri, Carmelo; Mandel, Victor Desmond; Seidenari, Stefania; Pellacani, Giovanni (Hereditary cancer in clinical practice, 2012)
Café au lait spots (CALS) are common dermatologic findings that can at the same time arise in a variety of pathologic conditions such as Neurofibromatosis type 1 (NF1), together with numerous hereditary syndromes for which they represent either diagnostic criteria or associated elements (McCune Albright, Silver-Russell, LEOPARD, Ataxia-Telangiectasia). A review of the literature also revealed two cases of association with NBCCS. We report here the case of a female proband with CALS associated to Nevoid Basal Cell Carcinoma Syndrome (NBCCS) with known PTCH1 germline mutation (C.1348-2A>G) who had been misdiagnosed with NF1 in her childhood because of 5 CALS and cutaneous nodules. The patient presented a giant cell tumor of the skin, palmar and calcaneal epidermoidal cystic nodules, odontogenic keratocystic tumors and deformity of the jaw profile. Her family history brought both her brother and father to our attention because of the presence of KCOTs diagnosed at early age: after genetic testing, the same PTCH1 germline mutation was identified in the three family members. Clinical criteria are used for discerning NF1 diagnosis (size, number and onset age), while there are no definite guidelines concerning CALS except for their presence. In our experience, we have noted an association of CALS with NBCCS; this seems interesting because we already know clinical criteria are a dynamic entity and can be modified by epidemiologic evidences.